NEUTRONIC ALAYSIS OF EUROPEAN SODIUM-COOLED FAST REACTOR USING OPENMC APPLICATION - Aria Ibnu Rachmat, Mochamad
The need for electrical energy is increasing. However, existing sources of electrical energy are still dominated by fossil fuels that are detrimental to the environment. Nuclear energy is an alternative fuel source that is being developed. The Generation IV International Forum is developing fourth-generation nuclear reactors. The European Sodium-cooled Fast Reactor (ESFR) is one of the fourthgeneration reactors. ESFR is designed to sustain chain fission for 5,6 years. This study aims to determine the improvement of the ESFR design to maintain chain fission for 10 years, determine the number and position of burnable poisons needed to reduce excess reactivity and compare the impact of different nuclear libraries on simulation. The reactor's ability to maintain the fission reaction can be determined by finding the value of the neutron effective multiplication constant. The research was conducted by the Monte Carlo method using OpenMC. OpenMC simulates a fullscale reactor according to the model created and gives output in the form of neutron effective multiplication constant data and changes in the composition of the reactor. The average effective k value for one year of activity from ESFR is 1,01525 with an average uncertainty of ±0,00043. This value is in good agreement with the existing reference results, with a difference of 0,0462%. From the results of the 1 year simulation, an ESFR reactor model capable of sustaining the fission reaction for 10 years was designed by providing additional fuel of 20% and burnable poisons in the form of 72 B4C 3% boron-10 pins packed in 18 assemblies. Five variations of poison pin length and three variations of poison assembly position in the reactor were designed. Of all the variations, the variation of the poison pin length of 80 cm with the variation of the assembly position placed between the inner fuel and the outer fuel zone reduced the reactivity to 3912,21327 pcm at the beginning of the reactor's service life. Lastly, using different nuclear libraries gives different average reactivity results but the same reactivity at timestep zero, around 3910 pcm. ENDF/B-VII.1 produced a 10-year average reactivity of 3202,07312 pcm, ENDF/B-VIII.0 library produced an average reactivity of 2952,19668 pcm, and simulations using the JENDL-5.0 library produced an average reactivity of 2756,01969 pcm. The difference is due to the different amounts of data in each library.